FINANCIAL AND INVESTMENT SUPPORT FOR THE DEVELOPMENT OF TERRITORIAL COMMUNITIES UNDER WARTIME CONDITIONS (INNOVATIVE ECONOMY, 2025)
Yushchyk Yu.V. FINANCIAL AND INVESTMENT SUPPORT FOR THE DEVELOPMENT OF TERRITORIAL COMMUNITIES UNDER WARTIME CONDITIONSPurpose. The aim of the article is to substantiate approaches to financial and investment support for the development of territorial communities of Ukraine in wartime conditions, taking into account limited resources, increased risks, and the need to ensure the viability of communities.Research methodology. The methodological framework of the study is based on systemic, institutional, structural and functional, and analytical approaches. Their application made it possible to reveal the essence of financial and investment support for the development of territorial communities during the wartime period, identify the specific features of the transformation of budgetary and investment mechanisms under heightened risks and uncertainty, and substantiate priority areas for improving resource management at the local level.Findings. The article clarifies the content of financial and investment support for the development of territorial communities as a multilevel system combining budgetary, investment, and institutional mechanisms of resource management under wartime conditions. It has been determined that martial law causes a transformation of the functional role of local budgets and a reorientation of financial flows toward social protection, support for internally displaced persons, maintenance of critical infrastructure, and security measures, while simultaneously limiting the possibilities for implementing investment development programs. The financial and investment instruments for community development have been systematized, and directions for improving the efficiency of resource use have been proposed.Originality. The theoretical approach to the interpretation of financial and investment support for the development of territorial communities as an integrated system of budgetary, investment and institutional mechanisms adapted to the conditions of the war economy has been deepened.Practical value. The proposed approaches can be used by local governments in forming financial policy, developing local development programs, preparing investment projects, and improving budget planning and systems for monitoring resource useKey words: financial and investment support, territorial communities, wartime period, wartime economy, local budgets, investment resources, financial capacity, project financing, community resilience, post-war recovery.
Keywords: financial and investment support; territorial communities; wartime period; wartime economy; local budgets; investment resources; financial capacity; project financing; community resilience; post-war recovery